Quantum Hardware Devices (QHDs): Opportunities and Challenges - Aziz Oukaira (IEEE Access)
Quantum Hardware Devices (QHDs) have marked a revolutionary leap in computational power, harnessing the principles of superposition, entanglement, and quantum interference to surpass classical processing capabilities. This review focuses on the core building blocks of quantum computing qubits, quantum gates, registers, and chipsets, while emphasizing the pivotal role of advanced architectures, such as Field-Programmable Gate Arrays (FPGAs) and Digital Signal Processors (DSPs), in optimizing quantum information processing. Despite their transformative potential, QHDs face critical hurdles, such as decoherence, Quantum Error Correction (QEC), scalability, and seamless integration with classical computing systems. Overcoming these challenges requires breakthroughs in materials science, cryogenic engineering, and quantum error mitigation. In addition, the development of high-fidelity quantum processors is essential for building robust Quantum Computing Systems (QCS) capable of solving problems beyond the reach of classical computation. This paper presents a comprehensive analysis of Emerging Quantum Technologies (EQT), examining their profound impact on cryptography, Artificial Intelligence (AI), Quantum Simulation (QS), and Secure Communication (SC). By reviewing state-of-the-art research and engineering innovations, we outline the roadmap for transitioning from experimental prototypes to large-scale, fault-tolerant quantum systems, paving the way for the next era of computing.